Osteonecrosis is associated with APOL1 variants in African Americans with systemic lupus erythematosus - Yip, Kevin; Akerman, Meredith; Fernandez Ruiz, Ruth; Leung, Nicole; Algasas, Huda; Qian, Yingzhi; Buyon, Jill P.; Divers, Jasmin; Izmirly, Peter; Belmont, Michael; Blazer, Ashira D. (Frontiers in Lupus, 2023)
Background/Purpose African Americans (AA) with systemic lupus erythematosus (SLE) are at risk for both kidney disease and Osteonecrosis (ON). Two Apolipoprotein L1 (APOL1) risk variants (RV), G1 and G2, have been associated with chronic kidney disease (CKD), hypertension, and microvascular disease in AAs, which are independent risk factors for ON. Accordingly, we investigated the association between APOL1 risk variant carriers and the prevalence of ON in AA SLE patients. Methods A cohort of 121 adult participants of self-reported AA ancestry and meeting at least four of the American College of Rheumatology (ACR) revised criteria for SLE were recruited from a high volume urban SLE clinical site. PCR/sequencing was used to stratify participants by APOL1 genotype. Medical records, including clinical notes and imaging reports, were retrospectively reviewed for documentation of ON. Association between the number of APOL1 risk variants with time to first ON was tested. Results In our cohort, 18 individuals developed ON; across the APOL1 genotype groups, 2/37 0RV, 11/59 1RV, and 5/15 2RV participants were affected. The mean time to ON was 27 years, 22 years, and 18 years in 0RV, 1RV, and 2RV carriers, respectively. An adjusted Cox regression model showed that carrying the APOL1 risk variants associated with shorter ON free survival with hazard ratios (HR) of 3.1 (95% CI: 1.6-6.2) and 9.6 (95% CI 2.4-37.8) for 1RV and 2RV carriers, respectively. 2RV carriers more often exhibited multiple and bilateral joint sites affected by ON. Disease duration was longer in ON-affected participants at 20.5 years compared to 9.0 years in those unaffected (p<0.001). In individuals who had received glucocorticoids, median cumulative prednisone equivalent dose was higher in ON-affected participants, though this did not reach statistical significance (18.7g vs. 9.0g; p-value=0.3). Conclusion Our analysis suggests a higher risk of osteonecrosis among African American SLE patients who carry the APOL1 risk variants. In addition, disease duration increased the rate of ON. Given the high frequency of the APOL1 risk variants in African Americans, APOL1 high-risk genotype carriers may represent an ON-vulnerable subgroup within the AA population. Further work is necessary to uncover the mechanism of this association.